Autels en pierre des « lieux de Dieu » tsu’Ssi à Bansoa (Cameroun) : entre art des environnements sacrés et dépôts picturaux rituels - Narcisse Santores Tchandeu (OpenEdition, 2019)
Overlooked in studies of stone structures in Cameroon, the Bansoa chiefdom in the center of the Bamileke plateau has revealed one of the largest concentrations of standing stones and cairns from the Grassland. It seems to be the reflection of the ancient foundation of a cultural practice perpetuated by a dense population, at the origin of a systematic marking of the space through the multiplication of “places of God” tsu’Ssi, conservatory of the sacralized ecosystems. At the heart of this heritage is the mythical figure of kam’Ssi, a kind of priest whose ritual processions cover the stone altars with pictorial elements, both symbolic and sensory. This relationship of the object of study to an actual makes it possible to appreciate this one in all its components and in consideration of the general history of stone structures in the region.